2018
DOI: 10.3389/fimmu.2018.01807
|View full text |Cite
|
Sign up to set email alerts
|

Carnosol Modulates Th17 Cell Differentiation and Microglial Switch in Experimental Autoimmune Encephalomyelitis

Abstract: Medicinal plants as a rich pool for developing novel small molecule therapeutic medicine have been used for thousands of years. Carnosol as a bioactive diterpene compound originated from Rosmarinus officinalis (Rosemary) and Salvia officinalis, herbs extensively applied in traditional medicine for the treatment of multiple autoimmune diseases (1). In this study, we investigated the therapeutic effects and molecule mechanism of carnosol in experimental autoimmune encephalomyelitis (EAE), an animal model of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 53 publications
2
37
0
Order By: Relevance
“…Previous studies have demonstrated that carnosol targets the NF-κB signaling pathway 40,59,60 , and our data showed that carnosol indeed inhibited NF-κB-mediated pro-IL-1β expression and IL-6 production in BMDMs treated with carnosol before LPS stimulating, indicating it could also prevent the inflammasome priming if added prior to the priming signal. Moreover, carnosol had no effect on expression of pro-IL-1β and IL-6 in BMDMs treated with carnosol after LPS stimulating, suggesting that carnosol can inhibit the priming stage but also plays a role in NLRP3 inflammasome activation step.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Previous studies have demonstrated that carnosol targets the NF-κB signaling pathway 40,59,60 , and our data showed that carnosol indeed inhibited NF-κB-mediated pro-IL-1β expression and IL-6 production in BMDMs treated with carnosol before LPS stimulating, indicating it could also prevent the inflammasome priming if added prior to the priming signal. Moreover, carnosol had no effect on expression of pro-IL-1β and IL-6 in BMDMs treated with carnosol after LPS stimulating, suggesting that carnosol can inhibit the priming stage but also plays a role in NLRP3 inflammasome activation step.…”
Section: Discussionsupporting
confidence: 71%
“…These results revealed that carnosol inhibits NLRC4 inflammasome activation but has no effect on AIM2 inflammasome activation. Previous studies have shown that carnosol disrupts the activation of the NF-κB signaling pathway, which largely controls NLRs and pro-IL-1β expression 40,48 . Our study revealed that when BMDMs were first treated with carnosol for 1 h and then stimulated with LPS for 4 h, carnosol treatment inhibited the expression of pro-IL-1β, TNF-α, and IL-6 in BMDMs (Fig.…”
Section: Carnosol Inhibits Nlrp3 Inflammasome Activation In Bmdms Thmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms that the activity of Punica granatum is due to the presence of active constituents like rosmarinic acid. Rosmarinic acid is also known to produce its activity due to its anti‐oxidative properties . The antioxidant effect of isolated compound was also investigated by analysis of various biochemical parameters, that is GSH, SOD, MDA and TNF‐α.…”
Section: Discussionmentioning
confidence: 99%
“…EAE was induced according to our previous study. 19 , 20 EAE mice were randomly divided into two treatment groups, 100 mg/kg PPE or solvent (PBS) were applied daily via oral gavage, at the first day of immunization, onset of disease (10 d), and peak of disease (16 d). After immunization, mice were assessed clinically in a blinded manner using a disease severity scale that is scored according to a 0–5 scale as described previously.…”
Section: Methodsmentioning
confidence: 99%